Rates and age trends in lumbar fusions in 2002 – 2017 – a descriptive analysis of 3,000 patients - Mikhail Saltychev; Petri Virolainen; Juri Kivelev; Janek Frantzen; Jaakko Rinne (Finland, 2022)
Objective
The objective of this study was to describe the change in rates and age averages among patients undergoing lumbar fusion during the last 20 years in a university hospital district located in Finland.
Methods
The data on 3,066 fusion surgeries were obtained from an electronic register between 2002 – 2017. The t-test, chi square, and regression analyses were used.
Results
In 2002 – 2017, 3,066 patients underwent lumbar fusion. The annual fusion rates grew in 16 years by 500%. The regression coefficient for annual rates of lumbar fusion procedures was 17.4 (95% CI 14.8 to 20.0, p-value <0.0001) procedure/year. In general, the patients were becoming older over time with regression coefficient 0.67 (95% CI 0.55 to 0.78, p-value <0.0001, R20.04) year/year.
Conclusions
In the studied cohort, the annual rates of lumbar fusions grew explosively during the last 16 years by 500% and the patients were 10 years older in 2017 than back in 2002. It seems, that if the trend observed here will continue then fusion patients may on average be even 20 years older in 2030 than they were in 2002. Surgeons and policy makers should take this probability under consideration when planning future techniques, rehabilitation, and allocation of funding.